A Corpus-Based Stylistic Identification of Lexical Density Profile of Three Novels by Virginia Woolf: The Waves, Mrs. Dalloway and To the Lighthouse - Shakir Hussein, Khalid; Abdul-Shareef Kadhim, Rawa (International Journal of Psychosocial Rehabilitation, 2020)
This paper is designed to present a short panorama of one of the stylistic markers which is that of lexical density. This marker is to be investigated within three literary texts of Virginia Woolf using the lexical density ratio with the aims of: (i) discovering how useful is the lexical density ratio in measuring the lexical resources of Virginia Woolf’s authorial style as it proceeds in her three novels: The Waves (1931), Mrs. Dalloway (1925),To the Lighthouse (1927) and (ii) comparing the lexical density ratios of these three novels so as to determine how, where and when the author’s lexical repertoire has prospered and/or declined. Downloading the digital texts, they are distributed into (43) samples: Mrs. Dalloway (13) samples, To the Lighthouse (14) samples and The Waves (16) samples. Each sample is of an approximate number of (5000) tokens. These samples are processed via Word Smith Tools (4.0) so as to obtain the number of tokens and lexical words. The obtained numerical data are then transformed into visual graphs via Microsoft Excel. It is found that Woolf’s The Waves seizes the majority of the higher lexical density ratios, whereas To the Lighthouse comes to score the lowest ratios. Mrs. Dalloway occupies an in between position where its curve stretches between that of The Waves and To the Lighthouse. Accordingly, The Waves has been proved to be the denser amongst the other two novels. A quality which gives it the shadow of being a difficult text.